The role of L1 in L2 speech production at different stages of L2 development: Evidence from L2 Chinese oral production of verb-phrase ellipsis by English and Korean speakers - Zhang, Lulu; Yuan, Boping (Frontiers in Psychology, 2022)
The article reports on an empirical study investigating the role of L1 at the initial and developmental stages of L2 speech production. It examines two types of Chinese verb- phrase-ellipsis, ΣP-ellipsis licensed by the auxiliary shi ‘BE’ and vP-ellipsis licensed by the other auxiliaries, in 45 English and 45 Korean adult speakers’ L2 Chinese speech production. An elicited imitation task was administered to L2 learners at beginner, intermediate and advanced Chinese proficiency levels. L1 influence is not observed at beginner levels, disconfirming an influential hypothesis by Schwartz & Sprouse (1994, 1996) that the L2 initial state is entirely based on the final state of learners’ L1. However, L1 influencebut appears at intermediate levels, and; at advanced levels, an asymmetry is found in the timing when L1 influnecedifferences between English and Korean learners’ production of ΣP-ellipsis and vP-ellipsis have disappears at different time in English and Korean learners’ oral production of verb-ellipsis and ΣP-ellipsised. It is proposed that the absence of L1 influence at beginner levels is due to a breakdown of syntax-stylistics interface and beginners’ difficulty in implementing checking and deleting operationsthe difficulty in procedures in their L2 oral production. The different timings of the disappearance of L1 influenceasymmetry in the two language groups found at advanced levels is attributedbelieved to be due to interactions between the persistence of L1 influence and the computational complexity involved in the target elliptical structures.